If cannons cannot fight hail, what else? - Jon Wieringa; Iwan Holleman (Meteorologische Zeitschrift, 2006)
Hail suppression is an uncertain meteorological subject in premature agricultural servitude. Commonly known is the method of seeding menacing cumulonimbus clouds with silver iodide by means of rockets or aircraft flares. Less discussed but widely practised alternatives are also reviewed here, in particular the useless but still quite popular practice to attempt destroying hailstones with explosives or with sound blasts from so-called hail cannons. The state of the art of hail formation detection with radar, and of hailfall probability nowcasting, is briefly reviewed.